Transición entre sistemas financieros bancarios y bursátiles. Una aproximación mediante modelo de Swithing Markov (2019)
Financial systems are considered to be one of the determinants of economic growth; these systems typically fall into two categories, banking and stock market. The literature on factors such as domestic credit to the private sector, traded shares (% of GDP), GDP per capita and inflation can be indicators of transition from one type of financial state to another. Therefore, the main contribution of this article is to determine the probability of transition between states of the banking financial system to a stock market and vice versa, present in emerging Latin American countries such as Mexico, Colombia, Brazil and Chile (belonging to the OECD). To perform these calculations, a twostate Switching Markov methodology is used as an analysis tool for the study period 2000-2016, with data from the World Bank in the financial information group. The results obtained reflect how over time, most countries remain in a single state, ie, despite international economic conditions there is no transition or changes in the financial system.